Thermodynamics of mixing for binary mixtures of 1-octanol and 1-decanol with n-dodecane and ternary mixture of (TBP + 1-octanol + dodecane) at T = (298.15 to 323.15) K. (November 2015) - Basu, M. (Ali); Samanta, T.; Das, D.
Highlights: Density and sound speed measurement of (alcohol + dodecane) and (alcohol + TBP + dodecane) mixtures between T = (298 and 323) K. Excess thermodynamic parameters calculated. Results interpreted in terms of intermolecular interactions. Abstract: Densities ( ρ ) and speed of sound ( u ) of the binary mixtures of 1-octanol and 1-decanol with dodecane and ternary mixture of 1-octanol + tributyl phosphate (TBP) + dodecane were measured at temperatures from (298.15 to 323.15) K over the entire composition range and at atmospheric pressure. Using these experimentally determined quantities, the excess molar volume ( V E ), excess isentropic compressibility ( κ s E ) for the binary mixtures and internal pressure ( p i ) of (alcohol + dodecane) binary mixtures have been calculated. The deviations shown by the excess quantities have been interpreted in terms of intermolecular interactions and structure of components. Using Hildebrand regular solution theory, several other parameters like the enthalpy and entropy of mixing of the binary components have been obtained. From acoustic measurements, the probable dimerization constant of the alcohols has also been determined. The values of these parameters give an indication of the subtle structural changes that occur in these binary mixtures.